Interactive White Board (IWB) in English Language Class - Istiqomah Wulandari (EDUCAFL : Journal of Education of English as Foreign Language, 2019)
Interactive White Board (IWB) in English Language ClassIstiqomah Wulandari, M. Ed.Study Program of English of Department of Languages and Literature, Faculty of Cultural Studies Universitas Brawijaya Malang Indonesiaistiqomah@ub.ac.idThe education sector has been affected by the growth of technology and has taken great advantages in connecting science and technology sides by side to reach the outmost result. One of the emerging technology devices used in teaching and learning in the classroom is the Interactive White Board (IWB) (Becta, 2004). Many researchers have been conducted to see how the implementation of IWB in the class room, such as the researches done by Cuthell in 2010 and by Kennewell (2006) shown that IWB adds some positive values in teaching and learning experiences. Based on that phenomenon, I decided to analyse and investigate the usage of IWB in the classroom and try to see their implications to TESOL particularly in area of technology use in language learning.Keywords: IWB, technology, English Class